RSV Disease Burden Among Children Under 2 Years of Age in the United States. (4th October 2017) - Arriola, Carmen; Reed, Carrie; Gerber, Susan I; Langley, Gayle E; Allen, Kristen; Anderson, Evan J; Openo, Kyle; Lynfield, Ruth; Bye, Erica; Reingold, Arthur; Daily, Pam; Thomas, Ann; et al.
Abstract: Background: Respiratory Syncytial Virus (RSV) is a major cause of respiratory hospitalizations in young children. Hospital discharge records have been used to estimate RSV-associated hospitalizations, but lacked individual-level laboratory-confirmed RSV data. We adapted an influenza-disease burden model that uses population-based surveillance and probabilistic multipliers to adjust for biases in disease detection to estimate RSV hospitalizations among children <2 years in the United States. Methods: From October 2014 through April 2015, we identified laboratory-confirmed RSV hospitalizations among children <2 years from 4 Influenza Hospitalization Surveillance Network (FluSurv-NET) sites. In addition, we identified the frequency and type of RSV testing performed among children with pre-selected RSV-associated acute respiratory illness (ARI) ICD-9 codes at each surveillance hospital. We used the surveillance catchment population (309, 000 children aged <2 years) to estimate age-specific (i.e., 0–2, 3–5, 6-11 and 12–23 months) rates of RSV-associated hospitalization, adjusting for detection probabilities. We then extrapolated these rates to the U.S. population using census data. Results: For the 2014–15 season, we identified 1, 554 RSV-associated hospitalizations in children <2 years. Overall, 16%, 22%, 24% and 29% of children with RSV-associated ARI codes, aged 0–2, 3–5, 6–11, and 12–23 months, respectively, were not tested for RSV during hospitalization. The age-specific adjusted RSV hospitalization rates per 100, 000 population were 1, 970 (95% confidence interval (CI):1, 757–2, 184), 897 (95% CI: 723–1, 070), 531 (95% CI: 439–622), and 358 (95% CI: 311–405), for children aged 0–2, 3–5, 6–11, and 12–23 months, respectively. Extrapolating to the U.S. population, an estimated 50, 705–67, 021 RSV-associated hospitalizations occurred in children <2 years. Conclusion: Our findings reiterate the importance of RSV as a cause of hospitalization in young children, especially those aged 0–2 months. This probabilistic approach can produce annual estimates of RSV disease burden to inform public health interventions and prevention strategies including RSV vaccines and monoclonal antibodies. Disclosures: E. J. Anderson, AbbVie: Consultant, Consulting fee; NovaVax: Research Contractor, Research support; Regeneron: Research Contractor, Research grant; MedImmune: Research Contractor, Research grant and Research support